2007
DOI: 10.1007/s12264-007-0004-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of practice versus information on the visual illusion

Abstract: Objective The Müller-Lyer illusion is a visual illusion in which a horizontal shaft with an inward-pointing chevron (fins-out) affixed to each end is perceived longer than a shaft with outward-pointing chevrons (fins-in). The goal of this study was to compare the effects of experience and knowledge about the Müller-Lyer illusion on participants' perceptual precision. Method Participants were undergraduate students (n = 108) who were not familiar with the Müller-Lyer illusion prior to the experiment. The task o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The instructions for the task were given orally [14] . A practice trial was given at the beginning of the first block of stimuli [15] .…”
Section: Methodsmentioning
confidence: 99%
“…The instructions for the task were given orally [14] . A practice trial was given at the beginning of the first block of stimuli [15] .…”
Section: Methodsmentioning
confidence: 99%
“…Training with up to 200 repetitions can attenuate the degree of misperception, albeit with some residual inaccuracy [58][59][60] . Interestingly, a combination of raised awareness with further practice can sometimes lead to greater accuracy 61 .…”
Section: Measurement Errormentioning
confidence: 99%
“…Second, if we find that the perceptual processing of the hair line affects eye-drawing performance, it remains open to question as to whether this perceptual-based drawing bias to draw the eyes too far up the head is mediated by the knowledge or lack thereof that the eyes are positioned half-way down the head. Previous research has demonstrated that explicit knowledge about the veridical properties of a stimulus can have the effect of reducing the magnitude of individuals’ experience of perceptual illusions (e.g., Khorasani, Fadardi, Fadardi, Cox, & Sharif, 2007). Thus, another goal of the present study was to investigate whether the potential effect that the presence versus absence of hair has on vertical eye-drawing accuracy differs between individuals with and without accurate schematic knowledge pertaining to the spatial positioning of the eyes.…”
Section: Perception Of Contextual Cues and Drawing: Effects Of The Pr...mentioning
confidence: 99%